Hematological Profile of Iron Overload in Rats Administered with Fruit Extract of Mahkota Dewa (Phaleria macrocarpa): Gambaran Hematologi Tikus Model Besi Berlebih yang Diberi Ekstrak Buah Mahkota Dewa (Phaleria macrocarpa) - Fransisca Dela Verna; Ari Estuningtyas (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2022)
Background: Repeated blood transfusions lead to an accumulation of iron that exceeds the body's iron storage capacity. Free iron is able to catalyze the formation of hydroxyl radicals that cause oxidative damage and cell death. The use of iron chelating medicines for iron chelation therapy is limited by side effects. Mangiferin is a natural bioactive compound with iron chelating and antioxidant activity. Mahkota dewa is a plant native to Indonesia that contains mangiferin. Objectives: The aim of this study was to evaluate the effect of mahkota dewa fruit extract administration on hematological profile of iron overload rats. Material and Methods: Thirty rats were divided into 6 groups: normal rats (N), iron overload rats (IO), iron overload rats rats given deferiprone (D), mangiferin (M), Mahkota dewa fruit extract at a dose of 100 mg/kg BW (PM1), or 200 mg/kg BW (PM2). Rats were given injection of iron sucrose 15 mg every 3-4 days for 8 weeks. At week 8, rats were sacrificed. Hematological analysis was performed in this study. Results: Iron overload condition caused by iron sucrose injection did not cause statistically significant changes in the haematological profile. Likewise, the administration mahkota dewa fruit extract at a dose of 100 or 200 mg/kg BW did not cause changes in the hematological profile. Conclusions: The administration of mahkota dewa fruit extract did not alter hematological profile of iron oveload rats.